Post-match sleeping behavior based on match scheduling over a season in elite football players. Issue 1 (2nd January 2018) - Carriço, Sandro; Skorski, Sabrina; Duffield, Rob; Mendes, Bruno; Calvete, Francisco; Meyer, Tim
ABSTRACT: Objectives: (1) To objectively monitor and describe sleeping patterns of elite football players after matches during a competitive season and (2) to describe the variability in sleeping patterns between these contexts. Methods: Actimetry was used to determine sleeping patterns of 25 elite players from 1 Portuguese First League (Liga NOS) club for at least 3 normal training days (TDs) as a baseline and then after various matches, including home (HM), away (AM), day (DM) and night (NM). Actimetry-derived sleep measures included total sleep duration (TSD), sleep onset latency, sleep efficiency (SE) and wake episode duration. Results: On TD, both TSD (6:36 h) and SE (85%) were below recommended healthy ranges of 7–8 h and >90%, respectively. TSD was even less after NM compared to both TD (–65 min) and DM (–65 min) ( P < 0.05), without differences between DM and TD ( P > 0.05). Additionally, TSD was greater in AM compared to HM (+77 min, P = 0.001). Conclusions: The primary findings of this study were the significant reduction in total sleep duration and later bedtime following (night) matches compared to normal training days.